2001
DOI: 10.1161/01.cir.103.9.1303
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Sodium Channel α- and β-Subunits in Rat and Mouse Cardiac Myocytes

Abstract: Background-Sodium channels isolated from mammalian brain are composed of ␣-, ␤ 1 -, and ␤ 2 -subunits. The composition of sodium channels in cardiac muscle, however, has not been defined, and disagreement exists over which ␤-subunits are expressed in the myocytes. Some investigators have demonstrated ␤ 1 expression in heart. Others have not detected any auxiliary subunits. On the basis of Northern blot analysis of total RNA, ␤ 2 expression has been thought to be exclusive to neurons and absent from cardiac mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

16
185
4
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 207 publications
(206 citation statements)
references
References 34 publications
16
185
4
1
Order By: Relevance
“…7C), and connexin-43 (Fig. 7C,6I, 6J) were localized to the intercalated disks, consistent with previous studies [11,23,29]. We found similar results in studies on acutely dissociated ventricular myocytes performed in parallel (not shown).…”
Section: Localization Of Sodium Channel α and β Subunitssupporting
confidence: 91%
See 3 more Smart Citations
“…7C), and connexin-43 (Fig. 7C,6I, 6J) were localized to the intercalated disks, consistent with previous studies [11,23,29]. We found similar results in studies on acutely dissociated ventricular myocytes performed in parallel (not shown).…”
Section: Localization Of Sodium Channel α and β Subunitssupporting
confidence: 91%
“…Prominent clustering of Na v 1.5 was detected at intercalated disks as well as at the cell surface (Fig. 6C, 6D), consistent with previous observations [20,21,29,30]. No changes in Na v 1.5 localization were observed in spite of increased protein expression (Fig.…”
Section: Localization Of Sodium Channel α and β Subunitssupporting
confidence: 91%
See 2 more Smart Citations
“…In line with other studies demonstrating T‐tubule remodeling in HF, we observed less deep Z grooves in TAC cardiomyocytes in addition to less clearly identifiable T‐tubule openings. Apart from the cardiac sodium channel Na V 1.5, neuronal sodium channel isoforms (ie, Na V 1.1, Na V 1.3, and Na V 1.6) are also thought to populate the T tubules 29, 30, 31, 32. Studies on expression and function of neuronal sodium channel isoforms during HF have shown varied results, most likely because of variations in species (rat, rabbit, dog) and HF model (pressure and/or volume overload and embolizations) used, with the most consistent observation comprising an upregulation of Na V 1.1 5, 23, 33.…”
Section: Discussionmentioning
confidence: 99%